Evaluation of efficacy of Caphosol in prevention and alleviation of acute side effects in patients treated with radiotherapy for head and neck cancers - Kiprian, Dorota; Jarzabski, Andrzej; Kawecki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: Oral mucositis is a common side effect of the oral mucosa due to anticancer therapy, especially for head and neck cancer. Caphosol is indicated for dryness of the mouth and oropharynx and treatment of mucositis due to irradiation or high-dose chemotherapy. The aim of the study was to evaluate the efficacy of Caphosol in preventing and alleviating mucositis due to radiotherapy in the head and neck region. Material and methods: Caphosol was used from the beginning of the irradiation and for two weeks more after the treatment was completed. Mucositis, xerostomia, and dysphagia were scored by radiotherapists. Subjective evaluation was made by patients. Caphosol was assessed in a non-blinded, matched clinical study. Each treatment arm consisted of 50 patients. The groups were similar. The only difference in the management protocol between the treatment arms was the use of Caphosol in the experimental arm. Results: A statistically significant difference in mean severity of early irradiation-induced side effects between the studied groups was observed with respect to: mucositis in the clinical target volume (CTV) area, mucositis in the increased dose (boost) area, dysphagia and xerostomia (p < 0.001 for all reactions). In the group of patients who used Caphosol, the mucositis was less intense, both in the CTV and in the boost area. Conclusions : The use of Caphosol reduces the severity of acute mucositis, dysphagia and xerostomia, exerting a positive effect on comfort in the oral cavity in patients irradiated for head and neck tumors.